2005
DOI: 10.1074/jbc.m409427200
|View full text |Cite
|
Sign up to set email alerts
|

Design of Soluble Recombinant T Cell Receptors for Antigen Targeting and T Cell Inhibition

Abstract: The use of recombinant T cell receptors (TCRs) to target therapeutic interventions has been hindered by the naturally low affinity of TCR interactions with peptide major histocompatibility complex ligands. Here, we use multimeric forms of soluble heterodimeric ␣␤ TCRs for specific detection of target cells pulsed with cognate peptide, discrimination of quantitative changes in antigen display at the cell surface, identification of virusinfected cells, inhibition of antigen-specific cytotoxic T lymphocyte activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 70 publications
5
70
0
Order By: Relevance
“…Thus, it appears to be possible to improve the avidity/affinity of the 264scTCR molecule for peptideloaded APCs by increasing its valency. The results of this experiment are in accord with recent observations made by Laugel et al (19) that tetrameric TCRs bind to peptide/MHC complexes better than monomeric TCRs. To evaluate the sensitivity of the 264scTCR/multimer as a staining reagent, we performed flow cytometric analysis with T2 cells loaded with various concentrations of cognate peptides.…”
Section: Sctcr Binding To Peptide/mhc Complexessupporting
confidence: 83%
See 3 more Smart Citations
“…Thus, it appears to be possible to improve the avidity/affinity of the 264scTCR molecule for peptideloaded APCs by increasing its valency. The results of this experiment are in accord with recent observations made by Laugel et al (19) that tetrameric TCRs bind to peptide/MHC complexes better than monomeric TCRs. To evaluate the sensitivity of the 264scTCR/multimer as a staining reagent, we performed flow cytometric analysis with T2 cells loaded with various concentrations of cognate peptides.…”
Section: Sctcr Binding To Peptide/mhc Complexessupporting
confidence: 83%
“…Thus, multimerization of the scTCR results in a reagent that binds to peptide/MHC complexes with a half-life of 20 min compared with ϳ7 s for the monomer. Similar observations related to changes in peptide/MHC binding kinetics with this type of molecule by multimerization have been reported by other laboratories (19,34). In addition, we have previously shown that dimerization of 264scTCR using an Ig H chain tail did increase both the K a and K d of the molecule while binding to the p53 264 -272 /HLA-A2.1 complexes.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Immunodominant PCD epitopes have not previously been identified, either from our own previous screens or from other studies (35)(36)(37). We find that previously identified candidates, as well as five new peptides, are naturally processed and presented by Ad-cdr2-immunized HLA-A2.1 transgenic mice.…”
Section: Discussionmentioning
confidence: 50%